Impactos no balanço hídrico decorrentes de mudanças no uso da terra na Bacia Hidrográfica do Rio Mundaú, Pernambuco - BRITO, Thyago Rodrigues do Carmo (2017)
The Caatinga is the only biome restricted to the Brazilian territory. Despite the great diversity of existing species and importance of conservation, this biome is the least studied and protected due to the anthropic pressure exerted. It is known that, together with global climate change, changes in land use can interfere in the water regime of various regions of the world. Thus, studies that determine the components of the hydrological cycle, such as: evapotranspiration, surface runoff, rainfall interception, deep drainage, capillarity ascension, among others are of paramount importance to predict how changes in land use will influence these processes. In order to evaluate changes in land use in the hydrological cycle, it is necessary to determine them in caatinga and cultivated areas (with pastures and/or agricultural crops) simultaneously. The objective of this work is to investigate the effect of changes in land use on the components of the hydrological cycle (evapotranspiration, surface runoff, drainage and capillarity ascension) in caatinga and pasture areas cultivated in São João, located in the Mundaú River watershed in Pernambuco’s Agreste. To obtain the date, collecting gutters shall be installed in the ground, in the caatinga and pasture areas, for the measurement of surface runoff. To measure soil volumetric moisture and soil matrix potential, sensors will be installed at depths of 10, 20, 30, 40, 50 and 60 cm. In the center of each area (pasture and caatinga) will be installed a metal tower with sensors to measure rainfall (Hydrological Services). The suppression of the caatinga by the pasture area contributed directly to the reduction of soil physical quality attributes, such as total pore volume, lower water retention, and increased soil density caused by trampling of animals due to compaction. During the two years of the experiment (October 2013 to September 2015), the final water storage balance in the pasture (9.23 mm) was higher than in the caatinga (4.9 mm). Total evapotranspiration in the caatinga (1,199.8 mm) was higher than in the pasture (1,195.5 mm). Evapotranspiration in both areas was directly proportional to rainfall, with its highest values occurring in the period from May to August. The highest production of plant biomass coincided with the months of higher rainfall indexes. The intensity of grazing also influences the production of vegetal biomass.